2011
DOI: 10.1007/s12603-010-0302-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and associations with falls, balance, mobility and functionality during hospital admission

Abstract: Evidence of reduced mobility was evident during GARU admission amongst older people assessed as malnourished. Considering the results, a larger study concerning nutritional status, functionality and falls in the hospitalized population is warranted. The influence of nutritional status upon a person's physical functioning should be considered more broadly in falls research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…These results can be expected as undernourishment, depression, and poor health are identified risk factors related to falls and poor physical performance 10,26,28,53. Falls were reported to be lower in protein/energy-supplemented older adults 54.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These results can be expected as undernourishment, depression, and poor health are identified risk factors related to falls and poor physical performance 10,26,28,53. Falls were reported to be lower in protein/energy-supplemented older adults 54.…”
Section: Discussionmentioning
confidence: 83%
“…However, assessment of nutritional status is rarely performed among older adult fallers 26. There is a positive relationship between falls and undernutrition among older adults that are hospitalized or residing at care homes 10,26. In contrast, this was not applicable to community-dwelling older adults 27…”
Section: Introductionmentioning
confidence: 99%
“…There is also an association between falls and undernourishment in elderly people who are either hospitalized or living in long-term care facilities [8]. Despite these consequences, several reports have shown that malnutrition remains under-recognized in the hospitalized elderly, where is no standard procedure is available for proper documentation due to insufficient awareness among healthcare professionals [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, usually older people admited to nursing homes are screened or assessed for either malnutrition or sarcopenia, but rarely for both conditions concurrently. In several populations, malnutrition and sarcopenia are present simultaneously and manifest clinically through a combination of decreased nutrient intake, decreased body weight, along with a decrease in muscle mass, strength and/or physical function [17].…”
Section: Malnutrition-sarcopenia Syndromementioning
confidence: 99%